The formation of copper type shear bands in AL-1MG and their influence on recrystallisation behaviour - Duckham, Alan (Centre for Materials Engineering, 2026)
Copper type shear band formation in AI-1 Mg and its influence on recrystallisation phenomena has been investigated. This study includes the development of a suitable plane strain compression (PSC) apparatus, and an analysis of the deformation and recrystallisation structures which evolve from a matrix of experiments incorporating temperature, strain and strain rate variables. A PSC test rig was purposely designed and built to facilitate the controlled high temperature deformation of aluminium specimens. The design of the apparatus ensured that strain distribution within a specimen is uniform while simultaneously limiting lateral spread. A small amount of lateral platen movement of the apparatus has been observed to cause asymmetric flow due to rotation of the plastic-rigid exit boundaries within the deforming specimens. Asymmetric flow compared to symmetric flow was found to have a negligible influence on the measured textures of the specimens studied.